L’effet de la température sur les propriétés(CMC) de tripolyphosphate de sodium (STPP) - MESSAAD, HALLAB, WEFA AHLAM (Université de m'sila, 2017)
We are interested in this work by studying the behavior of the conductivity surfactants (Sodium Tripolyphosphate) depending on the temperature in a range between 283.15K and 313.15Kwith 10K variation. Were used some conductivity measurements to determine the CMC of STPP for different concentration at T(283.15,293.15,298.15,303.15,313.15K), and we have noted that with increasing temperature and amount of STPP we obtained a high values of conductivity. And finally we found that the sulfuric acid does affect the critical micelle concentration of surfactant (STPP).
Keywords: Sodium Tripolyphosphate (STPP),conductivity measurement, temperature, critical micellar concentration (CMC)